If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 4 = 22 + -4x Reorder the terms: 4 + -7x = 22 + -4x Solving 4 + -7x = 22 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 4 + -7x + 4x = 22 + -4x + 4x Combine like terms: -7x + 4x = -3x 4 + -3x = 22 + -4x + 4x Combine like terms: -4x + 4x = 0 4 + -3x = 22 + 0 4 + -3x = 22 Add '-4' to each side of the equation. 4 + -4 + -3x = 22 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 22 + -4 -3x = 22 + -4 Combine like terms: 22 + -4 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| 3(9+2x)=21 | | 7x+9-4x=15 | | y+9=6-2y | | 35-x-24= | | 3x-2+4-x=-4 | | 4d+3= | | 5m-2m-2=m-10 | | 6n-4=3n+11 | | 4x^2=-9+12x | | 2x-5=x+7-3x | | 6x+80+18x-40=180 | | 13-3n=1 | | 108=6-6(1-6x) | | 63=91-p | | 6x+80+18x-40=1 | | 49p^2+70p+25=0 | | 16-3h=4 | | 77x^4-x^2+49=0 | | 8u+17u+6u-16u+18u=18 | | 2x(3x-4)(5x+6)= | | 40x+2=8 | | 67+21=x | | 13t+9t+10=352 | | -3x+-6=18 | | 55=.20(285-10e) | | 20x+4=40 | | 16z+18z=18 | | 54r^2+72r+24=0 | | 15x-12x=141 | | -3(2y+1)=3-6y | | X*x*x=24 | | 7-4(2x+3)=3 |